Sistem Informasi Pengaduan dan Pelayanan Berbasis Web pada Dinas Pekerjaan Umum dan Tata Kota di Kota Surakarta - Labib Dewa Saepudin; Moh. Muhtarom; Faulida Ely Nastiti (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
The cleanliness and beauty of the city is one of the attractions to visit a city. Maintenance of cleanliness, beauty and suitability of urban planning is the responsibility of each level II region, namely the city / or regency itself. In Surakarta City, the responsibility for cleanliness, beauty and urban planning is the responsibility of the Public Works and Spatial Planning Office, formerly known as DPU. This study aims to build an information system for the management and data collection of administrative information for facilities and infrastructure at SMP Negeri 15 Surakarta. This research uses UML as a system development method The results of the study provide results that the complaint and service information system is made to facilitate the community in providing complaints and requests for services, especially people in Surakarta City, system development is carried out using the UML method, the system is built by analyzing the shortcomings of the ongoing system, database design, system flow design and implementation system, with the application of the complaint and service system, public satisfaction with the services provided by the Surakarta City Government will increase so that public trust will also increase, and the system that has been formed is tested with the blackbox method. From the results of blackbox testing, from the login page, to the reporting page provides the expected results, so this system can be used.